(untitled) (Journal of Dhaka Medical College, 2020)
Background: Iron deficiency anemia (IDA) is one of the most frequent nutritional deficiency leading to morbidity and mortality in whole world. Oral iron therapy as well as intravenous (IV) iron therapy can be given to treat the IDA patients. Objective: To compare the efficacy and hematological changes of Oral and IV iron preparation in patients with uncomplicated iron deficiency anemia. Method: An interventional, prospective study in patients with uncomplicated IDA anemia receiving IV iron sucrose and Oral iron ferrous sulfate were included. Clinical history, baseline hemoglobin, anemia indices data were recorded in a case record form. A total number of 80 patients were enrolled in this study. 40 patients (Group A) were treated with IV iron sucrose and another 40 patients (Group B) were treated with oral iron ferrous sulfate. After therapy Hemoglobin level, RBC indices and adverse drug reactions (ADRs) were observed. Place and period of Study: Study was carried out in the Department of Hematology at Dhaka Medical College Hospital (DMCH), from July 2015 to June 2016. Results: The mean age of total participants was 35.77 ± 16.08 (range of 13 – 75 years). In this study female (72.5%) is predominant than male (27.5%). Oral and IV iron preparations significantly (P<0.0001) improved mean hemoglobin, anemia indices at the end of study. However, mean increase in hemoglobin were significant (P<0.0001) with IV iron sucrose (7.6 ± 2.9) gm/dl, as compared to Oral ferrous sulfate (6.4± 2.2)gm/dl, after 2 months of therapy. In this study Hemoglobin increases in group A (IV iron arm) almost 1mg/kg/week and in group B (oral iron arm) 0.8 mg/dl/week).Surprisingly, ADRs were more in patients treated with oral ferrous sulfate (38%) compared to iron sucrose (26%). Conclusion: IV iron sucrose improves hemoglobin, anemia indices and replenish iron stores rapidly and is well tolerated than oral iron preparations. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 175-181